Analysis of genetic variability by RAPD of strains isolated from soil and sludge impacted with industrial effluent - Silva, Ramon Gomes da; Pinhati, Fernanda Romanholi; Silva, Joab Trajano (Revista da Biologia, 2018)
The RAPD (Random Amplified Polymorphic DNA) is an ease and inexpensive tool to analyze microorganism in the environment. However, the protocol optimization is a crucial step to provide a suitable polymorphic profile. In the present work, bacteria obtained from activated sludge system and soil impacted with industrial effluent were studied by RAPD technique to provide genetic similarities relationships. A similarity level of 91.9% to 56%, between isolated sludge and soil were observed. A genetic starter was selected after protocol optimization and a characteristic polymorphic bands profile generated to isolated microorganisms. The presence or absence of the isolated microorganisms in samples can be controlled by using the obtained polymorphic profile.